Silvio Santos vem aí: a biografia-reportagem do “Patrão” - Mattos, Tiago Ramos e (2020)
Biography is a genre of speech that describes life. This biographical contemplation of life says a lot about human relationships in a particular way. Discourse genres of a biographical character have a type of refracting quality of human realities, which have resisted verisimilitude always because real life is their main element, regardless of the fictional heat to which they are exposed. Among these genres are intimate diaries, travel diaries, testimonies and/or statements, memories, autobiographies and the report. The report comes from a fact, which is described in a detailed way. The facts of life presented both in the biography, in a more extensive and elaborated way, and in the report, which enjoys a certain immediacy, will certainly emerge from an author and an authorship. The general objective of this work was to verify how, in the biography-reporting genre, the notions of author and authorship occur, regarding the distance or proximity between author and biographer, but mainly reflect how the voice of the biographer - character - influences the narrative and authorial composition of the author biographer. How can authorship in biography-reporting be circumscribed if we consider the characteristics of this genre, its style, its thematic content, its compositional construction, as well as the constitutive characteristics of the biography and journalistic reporting genre? In order to answer this question, we analyzed the corpus Silvio Santos – The trajectory of the myth (2017), from which, at the beginning, a differentiated biography is perceived: the book is written based on reports recorded throughout Silvio Santos' life. Therefore, it consists of two main authors: Fernando Morgado and Silvio Santos himself. The results of the analyzes gave the book the status of biography-reporting, a hybrid of two genres of discourse, through a double authorship. As a biography, it enjoys an innate heterogeneity in this genre of discourse: it is rich in manifest intertextuality and constitutive intertextuality. The biographical narrative implies a construction coming from the chronological format, a characteristic of the reporting genre. It presents a thematic content constituting the circulation, reception and production of these statements, a style that is sometimes pictorial, sometimes linear, filled with rhetorical figures of speech and a bipartite compositional construction between the statements of the biographer and the biographical narrative